LOCAL DEMOCRACY AND MEANINGFUL PARTICIPATION IN THE ROAD TO 2024 SIMULTANEOUS REGIONAL ELECTIONS - Azizah, Naili; Rosita, Dian; Lestari, Inesa Rahma; Izziyana, Wafda Vivid (Semarang Law Review (SLR), 2024)
The 2024 Simultaneous Regional Elections (Pilkada) must basically be able to guarantee and maintain public participation in various considerations for decision-making, campaigns, and public hearings, including in all processes leading up to the implementation of the Simultaneous Regional Elections. Public participation is not just the public giving their right to vote in the General Election/Pilkada, but more than that, Public Participation should ideally be meaningful participation in the planning, process and implementation of the Pilkada. The Research Method Using This research approach uses an analytical approach, namely analyzing cases that occurred in the preparation process for the 2024 Pilkada. The results of the study found that policy makers have not fully seen public participation as a necessity. This is illustrated by the sudden and seemingly rushed policy-making on the Revision of the Pilkada Law. In addition, many candidates offered from the elite are not from local communities who do have a role in development in the local area. This is homework to realize a local democracy that is advanced and considered.